Molecular detection and characterization of tick-borne protozoan and rickettsial pathogens isolated from cattle on Pemba Island, Tanzania - Aaron Edmond Ringo (2018)
© 2018 Elsevier GmbH Tick-borne diseases cause significant losses to livestock production in tropical and subtropical regions. In Tanzania, detailed studies on tick-borne pathogens in cattle using sensitive molecular detection methods are scarce. In this study, we investigated the occurrence of Theileria spp., Babesia spp., Anaplasma spp. and Ehrlichia spp. in 245 blood samples collected from cattle on Pemba Island, Tanzania. We used polymerase chain reaction (PCR) and gene sequencing to detect and identify pathogens. PCR screening revealed overall infection rates of 62.4% for Theileria spp., 17.6% for Babesia bigemina, 15.9% for Anaplasma marginale, 7.4% for Ehrlichia ruminantium and 4.5% for Babesia bovis. Further analysis using sequences of Theileria spp. 18S rRNA revealed infection of cattle with Theileria mutans (68.6%), Theileria taurotragi (48.4%), Theileria parva (41.2%), and Theileria ovis (1.9%). Co-infections of cattle, with up to six tick-borne pathogens, were revealed in 46.9% of the samples. Sequence analysis indicated that T. parva p104, E. ruminantium pCS20 and A. marginale MSP-5 genes are conserved among cattle blood samples in Pemba, with 99.3%–100%, 99.6%–100% and 100% sequence identity values, respectively. In contrast, the B. bigemina RAP-1a and B. bovis SBP-2 gene sequences were relatively diverse with 99.5%–99.9% and 66.4%–98.7% sequence identity values respectively. The phylogenetic analyses revealed that T. parva p104, E. ruminantium pCS20 and A. marginale MSP-5 gene sequences clustered in the same clade with other isolates from other countries. In contrast, the B. bigemina RAP-1 and B. bovis SBP-2 gene sequences showed significant differences in the genotypes, as they appeared in separate clades. This study provides important data for understanding the epidemiology of tick-borne diseases, and is expected to improve the approach for diagnosis and control of tick-borne diseases in Tanzania.